National Education Policy (NEP) 2020 on Transforming Education A Critical Analysis of Recommendations on School, Teacher and Higher Education - Dey, Niradhar (JOURNAL OF INDIAN EDUCATION, 2022)
The National Education Policy 2020 had been notified on 29th July 2020 after 34 years of the implementation of National Policy on Education (1986). Detail structural and pedagogical changes have been recommended in Early Childhood Care and Education, School Education as well as Teacher and Higher Education. Beginning from the fundamental principles of the constitution of NEP 2020, a sign of transformation in education and its implementation practices have been focused in every part of NEP 2020. This article focuses on the history of educational development of India and analyses some of the major recommendations of NEP 2020 on different aspects. The article discusses the vision of transforming education by implementing NEP 2020 in the major three areas of its recommendations such as School, Teacher and Higher Education. A critical analysis has also been made against the specific recommendations in each section of the policy and a consolidated summary and discussion has also been made.